Pengaruh Model Pembelajaran Project Work terhadap Keterampilan Proses Sains dan Hasil Belajar Kognitif - Saryono, Teguh (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
The objectives of this research are: 1) to describe the students' science process skills after being taught by the project work learning model in class VII SMP Sawunggaling; and 2) to determine the effect of the project work learning model on the cognitive learning outcomes of grade VII students of SMP Sawunggaling. This type of research is a quasi-experimental research design using pre-test-post-test control group design. The population in this study were all seventh grade students of SMP Sawunggaling in the 2018/2019 academic year. The research sample was class VIIA as the experimental class and class VIIB as the control class. Determination of the sample is done by using the Cluster Random Sampling technique. Data analysis techniques are descriptive and t-test. Based on the results of data analysis, science process skills showed that the first meeting in the experimental class was 84.88% in the very skilled category, while at the second meeting it was 91.36% in the very skilled category. The test data of students' cognitive learning outcomes showed the average value of the experimental class was 79.56% with classical completeness 86.36%, while in the control class the average value was 65.22% with classical completeness 56.52%. The test data of students' cognitive learning outcomes were then analyzed using t-test, obtained tcount of 2.39 and ttable of 1.68. Because tcount > ttable, the conclusion of this study is that there is an effect of the project work learning model on students' cognitive learning outcomes.